Upaya Peningkatan Pemberdayaan Ibu Rumah Tangga Melalui Inovasi Produk Dan Penjualan Pada Umkm Kerupuk Emping Mlinjo - Armayang Nindytarani; Mukhammad Luqman Hakim (JPPMI: Jurnal Pelayanan dan Pemberdayaan Masyarakat Indonesia, 2026)
Emping mlinjo crackers SMEs are include in community empowermwnt, especially for empowering housewives. Emping mlinjo crackers SMEs are the mainstay of the economy of housewives in Puhrejo Hamlet. Community service activities carried out are in the form of innovation activities aimed at conducting training and assistance efforts in product development and sales. The activity has a target that SMEs actors can increase their abilities and income from product innovation and sales. The method of this activity uses the ABCD method which focuses on asset development in the form of innovation.